2011
DOI: 10.1103/physrevb.84.085442
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity reduction in core-shell nanowires

Abstract: Nanostructuring of thermoelectric materials bears promise for manipulating physical parameters to improve the energy conversion efficiency of thermoelectrics. Using nonequilibrium molecular dynamics, we investigate how the thermal conductivity can be altered in core-shell nanocomposites of Si and Ge. By calculating the phonon vibrational density of states and performing normal mode analysis, we show that the thermal conductivity decreases when phonon-transport becomes diffusion-dominated and unveil a competiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
85
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 31 publications
8
85
1
1
Order By: Relevance
“…For instance, by etching the surface of silicon NWs, it has been experimentally demonstrated that thermal conductivity of Si NW can be reduced more than two orders of magnitude compared with bulk Silicon [5,6]. Moreover, remarkable reduction of thermal conductivity in core-shell [7][8][9][10], tubular [11,12], and surface-decorated [13] NWs has also been reported through various kinds of interface and surface engineering.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, by etching the surface of silicon NWs, it has been experimentally demonstrated that thermal conductivity of Si NW can be reduced more than two orders of magnitude compared with bulk Silicon [5,6]. Moreover, remarkable reduction of thermal conductivity in core-shell [7][8][9][10], tubular [11,12], and surface-decorated [13] NWs has also been reported through various kinds of interface and surface engineering.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, by etching the surface of silicon NWs, it has been experimentally demonstrated that thermal conductivity of Si NW can be reduced more than two orders of magnitude compared with bulk Silicon [5,6]. Moreover, remarkable reduction of thermal conductivity in core-shell [7][8][9][10], tubular [11,12], and surface-decorated [13] NWs has also been reported through various kinds of interface and surface engineering.Previous studies [7][8][9] on the reduction of thermal conductivity in core-shell NWs mainly focus on Si/Ge core-shell NWs, which is quite intuitive as Ge is a low thermal conductivity material compared to Si [14]. However, in experimental realizations, the NWs synthesised are Ge/Si core-shell NWs [1][2][3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many experimental investigations have been carried out to synthesize and characterize different kinds of core/shell structures such as ZnO/ZnS [13], ZnO/CdS, [14] GaN/GaP, ZnO/TiO2 [15,16], CdSe/CdS [17,18], PbSe/CdSe [19,20], ZnS/CdS [21][22][23][24][25], CdS/ZnS [21,26,27], Ge/Si [28]. Both the classical molecular dynamics (MD) and density functional theory (DFT) methods have been used extensively to study the electronic [29][30][31][32][33][34][35], optical [29,36] and thermal [37][38][39][40][41][42][43][44][45][46][47][48] properties of the core/shell nanostructures. In contrast, mechanical properties of the core/shell nanostructures have so far not been investigated in details.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the individual silicon nanowires, Si/Ge CSNWs have evident advantages because the covering layer offers the possibility of a partial and internal charge separation, an efficient passivation of the surface trap states and so on. 7 Up to date, significant progresses for Si/Ge CSNWs both experimentally [8][9][10][11][12][13][14] and theoretically [15][16][17][18][19][20][21][22][23][24][25][26][27][28] have demonstrated that the thermal transport properties of Si/Ge CSNWs can be modified at room temperature compared to that of the bare Si or Ge nanowires. Classically, the standard macroscopic approach describing heat transport in semiconductors is the well-known Fourier's law, i.e., J = −κ∇T, where J and ∇T are the heat flux density in the material and the temperature gradient, respectively.…”
Section: Introductionmentioning
confidence: 99%